Cyclohexanone and Phenolic Acid Derivatives from Endophytic Fungus Diaporthe foeniculina - Lu, Xiuxiang; Zhang, Yanjiang; Zhang, Wenge; Wang, Huan; Zhang, Jun; Wang, Sasa; Tan, Haibo (Frontiers in Chemistry, 2021)
Chemical investigation of the EtOAc extract of an endophytic fungus Diaporthe foeniculina SCBG-15, led to the isolation of eight new cyclohexanone derivatives, foeniculins A-H (1-8) and three new phenolic acid derivatives, foeniculins I-K (9-11). Their structures were extensively established on the basis of 1H and 13C NMR spectra together with COSY, HSQC, HMBC, and NOESY experiments. The absolute configurations were confirmed by the application of quantum chemical ECD calculations and single-crystal X-ray diffraction experiments. Moreover, the isolated compounds 1-11 were evaluated to understand their effects in vitro cytotoxic activity and antibacterial activity.